Teaching Object-Oriented Modelling using Concept Maps - Sien, Ven (Electronic Communications of the EASST, 2011)
As one of the most important tasks in object-oriented analysis and design (OOAD) is the abstraction of the problem domain into specific concepts or objects, information technology (IT) students need appropriate skills of abstraction in order to identify the essential concepts and relationships within a problem domain. However students in higher education generally find difficulty performing abstractions of real-world problems within the context of OOAD. Concept mapping is a popular tool used in education for facilitating learning, comprehension and the development of knowledge structures. We have successfully adopted concept maps as stepping-stones to assist students in constructing class and sequence diagrams. In this paper, we present a framework for teaching object-oriented (OO) modelling using concept maps. This framework – comprising four teaching modules – could be integrated into existing OOAD courses at the undergraduate or postgraduate level, and OOAD workshops to help software engineering educators resolve some of the difficulties they face in trying to teach OOAD. We also report results of an evaluative study on the effectiveness of integrating concept mapping techniques into an introductory OOAD course.